Transnational Cooperation in Criminal Matters and the Guarantee of a Fair Trial: Approaches to a General Principle - Sabine Gless (Utrecht Law Review, 2013)
The right to a fair trial has grown in importance over the past few decades as criminal procedures and human rights law have aligned themselves more and more closely. A core aspect of our current European understanding of a ‘fair criminal trial’ is the so-called ‘equality of arms’, which requires that each party be given a reasonable opportunity to present his case under conditions that do not place him at a substantial disadvantage vis-à-vis his opponent. In cases which affect more than one jurisdiction – either because an alleged crime causes damage in different countries, evidence is located abroad or for some other reason – the accused and his defence lawyer may be left without any such a guarantee in the legal ‘black hole’ between the protections that are normally offered by each of the jurisdictions involved, albeit separately.The situation is not one of a dramatic alteration of legal frameworks; instead, it is the small encroachments caused by transnational cooperation that matter and which can be summed up on the basis that domestic and foreign prosecution authorities have, effectively, closed the circuit between them. These authorities are now embedded in formal networks which would have, for instance, the possibility to forum shop (i.e. to choose the ‘best place’ to prosecute). The emerging EU legal framework that has been built on mutual recognition and installing new central agencies has added to the problems faced by the defence. Moreover, the existing legal regimes designed to protect do not grant ‘equality of arms’ in the space between jurisdictions: national law usually provides few answers and international law, including the likes of the ECHR or the EU Charter on Fundamental Rights, do not offer many solutions, either.This article therefore argues that an aspiring ‘right to a fair trial’ or, rather, an entitlement to equality of arms as a general principle of transnational criminal justice that would empower the defendant and his defence to present their case under conditions that do not place the accused at a substantial disadvantage in transnational cases, would be highly beneficial and serve to fill in a missing piece in the puzzle of achieving ‘a world wholly governed by law’.